C-Reactive Protein and Risk of Parkinson's Disease: A Systematic Review and Meta-Analysis - Qiu, Xiaohui; Xiao, Yousheng; Wu, Jingjing; Gan, Lu; Huang, Yanning; Wang, Jin (Frontiers in Neurology, 2019)
Background: C-reactive protein (CRP) has been identified as a common inflammation-related cytokine. Although publications indicate that CRP is associated with the pathogenesis of neurological disorders and deemed to be a “risk factor” for Parkinson’s disease (PD), the evidence exists still indefinitely. Here, we performed a systematic review with meta-analysis synthesizing all the eligible studies on serum, plasma, and cerebrospinal fluid (CSF) CRP levels and PD risk to investigate the potential relevance. Methods: A systematical search up to October 2018 was performed via PubMed, Embase, Science Direct, ISI Web of Science as well as three Chinese medical databases: China National Knowledge Infrastructure database (CNKI), VIP database and WanFang database. Risk was assessed by standardized mean difference (SMD) with 95% confidence interval (CI) to investigate the involvement of CRP levels in PD patients. Results: Twenty-three eligible case-control studies involving 4598 individuals (2646 PD patients and 1932 healthy controls) were incorporated into this meta-analysis. Results have indicated significant increase of CRP levels in PD subjects when compared with control groups in serum (SMD = 1.115, 95% CI 0.619-1.61, P < 0.001), CSF (SMD = 1.127, 95% CI 0.133-2.120, P = 0.026) as well as whole blood (SMD = 1.071, 95% CI 0.715-426, P < 0.001). Conclusions: This meta-analysis revealed that PD is associated with an increase of CRP levels. CRP might be a risk factor for PD or PD leads to an inflammatory response.